Deposition of ZnO Layers Using Planar Reactive Magnetron System - Daugėla, J.; Joneliūnas, S.; Jotautis, A.; Naujokaitis, R.; Klovaitė, E. (Elektronika ir Elektrotechnika, 2005)
Properties of ZnO films deposited using radiofrequency and direct current magnetron sputtering systems with ZnO and metallic Zn targets in oxygen and oxygen-argon gas mixture atmosphere on glass K-8 substrates were experimentally investigated. The influence of Cu impurities and ZnO layers post deposition thermal annealing is estimated. The optimal growth technological conditions of highly oriented polycrystalline piezoelectric ZnO films using planar reactive magnetron system are defined. The parameters of formed SAW delay lines were approximately equal of theoretically calculated for monocrystalline ZnO. Ill. 7, bibl. 5 (in English; summaries in Lithuanian, English and Russian).